1987
DOI: 10.1590/s0074-02761987000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estadisticas vitales de Rhodnius neivai Lent, 1953 (Hemiptera: Reduviidae) en condiciones experimentales

Abstract: A statistical evaluation of the population dynamics of R. neivai is based on six cohorts experiments conducted under controlled laboratory conditions. Two blood sources were offered to animals: rabbit and hen. Egg hatching, nymphal development time and mortality, adult longevity and age-specific mortality, female age-specific fecundity and fertility were determined. In addition, some population parameters were evaluated, such as: life expectancy, intrinsic rate of natural increase, net reproduction rate, finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…The statistics of reproduction characteristics and its comparisons with other species are summarized in Table IV. The interval between entering the adult stage and first laying was two weeks, these results are in line with the indicated for others species of triatomines: between 9 days and 4 weeks after its entering to the adult stage (Rabinovich 1972a,b, Feliciangeli & Rabinovich 1985, Cabello et al 1987.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The statistics of reproduction characteristics and its comparisons with other species are summarized in Table IV. The interval between entering the adult stage and first laying was two weeks, these results are in line with the indicated for others species of triatomines: between 9 days and 4 weeks after its entering to the adult stage (Rabinovich 1972a,b, Feliciangeli & Rabinovich 1985, Cabello et al 1987.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of absolute mortality all our results showed figures smaller than the indicated for other species of triatomines (Rabinovich 1972a, Feliciangeli & Rabinovich 1985, Cabello et al 1987.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…were shorter on cohorts reared on mammals (mice) than on those reared on birds (chicken, pigeons or hens). However, Cabello et al (1987) reported a longer life cycle of Rhodnius neivai fed on rabbits than fed on hens. In the current study, the average development time of the cohorts of M. picturatus fed on hens (196.8 ± 15.8 days) and fed on rabbits (189.5 ± 22.9 days) were not significantly (P > 0.05) different.…”
Section: Discussionmentioning
confidence: 98%